Tanggung Jawab Kapitalis: Strategi H&M Menanggulangi Dampak Negatif Industri Fast Fashion - Maria Fransiska Oktavia Nugraheni; Reni Windiani; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2022)
Most of the international relations research examines the state as an actor with all the issues it faces. However, this study discusses more about the business entity which is H&M in its strategy to overcome the negative impact of the fast fashion industry on the global environment. Fast fashion is a business strategy that used to balancing the demand of the customer with company’s capabilities through quick response strategy as implemented by H&M. The negative impact of the fast fashion industry including the environmental and humanitarian sectors, which have a huge impact for humans. This study uses liberalism capitalist theory and creating shared value concept as its theoretical approach to analyze H&M’s strategy. The researcher uses a qualitative research methodology compiled through a literature study. The data was taken from previous studies and combined information from related official documents such as the H&M Sustainable Report and the H&M Foundation Annual Report with relevant news. The result of this study reveals that H&M which is an element of capitalist has also implemented strategies to overcome the negative impacts of the fast fashion industry through the H&M Sustainable program and the H&M Foundation Global Program for Equality which uses creating shared value concept. This research contributes to the negative impact of the fast fashion industry and the strategies undertaken by H&M as a capitalist industry to show its commitment to sustainable development.